The Impact of National Health Insurance Scheme (NHIS) on Enhancement of Access to Health Services in Tertiary Institutions in Nigeria: A Study of Selected Federal Tertiary Institutions in Kogi State - Zekeri Sunday (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study investigates the impact of the National Health Insurance Scheme (NHIS) on staff's access to healthcare services in selected federal tertiary institutions in Kogi State, with a particular focus on the Federal University Lokoja. The research is anchored on the premise that improved access to affordable healthcare enhances staff productivity, welfare, and institutional efficiency. Despite the introduction of NHIS to facilitate Universal Health Coverage (UHC), challenges such as limited awareness, low enrolment, inadequate service delivery, poor funding, and dissatisfaction with healthcare providers persist within Nigerian tertiary institutions. The study adopts a descriptive survey design and employs both primary and secondary data. A multi-stage sampling technique was used to select 165 academic and non-academic staff, and structured questionnaires were the primary data collection instrument. The objectives of the study include assessing awareness and enrolment levels, evaluating access to quality healthcare services, identifying implementation challenges, and determining the overall impact of NHIS on service delivery. Preliminary findings suggest that while NHIS has moderately improved access to healthcare, gaps in awareness, service quality, and administrative efficiency hinder its effectiveness. The study concludes that strengthening NHIS implementation through improved sensitisation, transparent administration, adequate funding, and enhanced provider accountability is essential for achieving equitable and efficient healthcare delivery in tertiary institutions. Recommendations were proposed to policymakers, NHIS administrators, and institutional management to optimise healthcare access and staff welfare